ChemInform Abstract: Structural, Magnetocaloric, Electrical Properties and Theoretical Investigations in Manganite La0.67Sr0.1Ca0.23MnO3 Type Perovskite. Issue 35 (September 2015) - Mohamed, Za.; Abassi, Mounira; Tka, E.; Dhahri, J.; Hlil, E. K.
Abstract Review: 42 refs.